Study of adaptive states and variability of phenological development of introduced woody plants of the genus Berberis L. in the conditions of the Altai Botanical Garden - Isakova , E.; Vinokurov , A.; Danilova , A.; Lagus, Olga (Fundamental and Experimental Biology, 2025)
The article considers the features of phenological development and adaptive capabilities of the genus Berberis L. during primary introduction in the conditions of the Altai Botanical Garden. The characteristics of the origin of the collection taxa of the genus are given, the taxonomic composition of the collection fund of the genus Berberis L. as of 2025 is verified. The introduced species are divided by soil-geographical origin, where the introduced species are distributed into 5 groups. An introduction assessment of the genus Berberis L. is given based on ecological-geographical, morpho-biological characteristics. The adaptive potential of introduced species is assessed based on long-term phenological observations of the development of introduced species, where the full development cycle is established. Based on the results of the assessment of the prospects of introduced species, two groups of species prospects were identified: promising (83%) of the collection fund and less promising (17%). Based on this assessment , introduced species are recommended for use in phytomelioration , gardening and park construction, as ornamental and fruit crops in Eastern Kazakhstan.